Fast Skeletal Muscle Troponin Activation Increases Force of Mouse Fast Skeletal Muscle and Ameliorates Weakness Due to Nebulin-Deficiency - Lee, Eun-Jeong (Public Library of Science, 2013)
The effect of the fast skeletal muscle troponin activator, CK-2066260, on calcium-induced force development was studied in skinned fast skeletal muscle fibers from wildtype (WT) and nebulin deficient (NEB KO) mice. Nebulin is a sarcomeric protein that when absent (NEB KO mouse) or present at low levels (nemaline myopathy (NM) patients with NEB mutations) causes muscle weakness. We studied the effect of fast skeletal troponin activation on WT muscle and tested whether it might be a therapeutic mechanism to increase muscle strength in nebulin deficient muscle. We measured tension–pCa relations with and without added CK-2066260. Maximal active tension in NEB KO tibialis cranialis fibers in the absence of CK-2066260 was ∼60% less than in WT fibers, consistent with earlier work. CK-2066260 shifted the tension-calcium relationship leftwards, with the largest relative increase (up to 8-fold) at low to intermediate calcium levels. This was a general effect that was present in both WT and NEB KO fiber bundles. At pCa levels above ∼6.0 (i.e., calcium concentrations <1 µM), CK-2066260 increased tension of NEB KO fibers to beyond that of WT fibers. Crossbridge cycling kinetics were studied by measuring k(tr) (rate constant of force redevelopment following a rapid shortening/restretch). CK-2066260 greatly increased k(tr) at submaximal activation levels in both WT and NEB KO fiber bundles. We also studied the sarcomere length (SL) dependence of the CK-2066260 effect (SL 2.1 µm and 2.6 µm) and found that in the NEB KO fibers, CK-2066260 had a larger effect on calcium sensitivity at the long SL. We conclude that fast skeletal muscle troponin activation increases force at submaximal activation in both wildtype and NEB KO fiber bundles and, importantly, that this troponin activation is a potential therapeutic mechanism for increasing force in NM and other skeletal muscle diseases with loss of muscle strength.